2006
DOI: 10.1002/ajmg.b.30345
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity‐dependent genetic association of ABCA2 with sporadic Alzheimer's disease

Abstract: A recent study demonstrated a significant genetic association between the ATP-binding cassette transporter A2 (ABCA2) and the risk for Alzheimer's disease (AD) in a large Caucasian sample. The rare T allele of the synonymous exonic single nucleotide polymorphism (SNP) rs908832 was overrepresented in early-onset AD patients as compared to cognitively healthy controls. Here we confirm the association of rs908832 with AD in a Western European population (n = 291, P = 0.008). In a second sample from Southern Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…This led us to use genetic tools to investigate how cholesterol dyshomeostasis may lead to AD. We focused our attention on the ATP-binding cassette transporter-2 (Abca2) for two reasons: (i) Abca2 has been genetically linked to Alzheimer disease (22,23) and (ii) Abca2 plays a role in intracellular sterol trafficking (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This led us to use genetic tools to investigate how cholesterol dyshomeostasis may lead to AD. We focused our attention on the ATP-binding cassette transporter-2 (Abca2) for two reasons: (i) Abca2 has been genetically linked to Alzheimer disease (22,23) and (ii) Abca2 plays a role in intracellular sterol trafficking (24).…”
mentioning
confidence: 99%
“…The endosomal-lysosomal pathway is also known to be the major site of A␤ generation (33)(34)(35) and further studies demonstrated a co-localization of Abca2 and APP in intracellular vesicles of neuroblastoma cells (36). The clinical relevance of Abca2 is suggested by two independent studies that strongly linked the identical single nucleotide polymorphism to AD (22,23). However, the underlying molecular mechanism is still unclear.…”
mentioning
confidence: 99%
“…AD predisposition is associated, albeit controversially, with circulating and cerebrospinal fluid (CSF) cholesterol levels and linkage to cholesterol homeostasis genes, including the APOE e4, CYP46A1, and ABCA1 genes (40). Recently, a single-nucleotide polymorphism within exon 14 of Abca2 (rs908832) was linked to earlyonset AD (26,43). This mutation produces elevated cholesterol levels in CSF, a risk factor for AD (43).…”
mentioning
confidence: 99%
“…Recently, a single-nucleotide polymorphism within exon 14 of Abca2 (rs908832) was linked to earlyonset AD (26,43). This mutation produces elevated cholesterol levels in CSF, a risk factor for AD (43). The effects on CSF cholesterol and AD age of onset are shared by mutants of Abca1, the closest relative of Abca2; both are cholesterolresponsive genes with identity in a C-terminal region (VFVNFA) associated with the ABCA1-apoA1 interaction and lipid efflux (11,19).…”
mentioning
confidence: 99%
“…ABCA2 levels were shown to be elevated in the temporal and frontal regions of the brain, areas frequently associated with AD pathology. Recently, a synonymous SNP in exon 14 of ABCA2 (rs908832) was determined to have a significant linkage with early-onset AD [80,81] and an impact on cholesterol in cerebrospinal fluid [81]. This transporter was also shown to localize in specific areas of the brain associated with adult neurogenesis and AD pathology (subventricular zone lining of the lateral ventricles and the dentate gyrus of the hippocampus) and in GABAergic and glutamatergic neurons [82].…”
Section: The Alzheimer Disease Link To Abca1 and Abca2mentioning
confidence: 99%